Applying the Problem-Based Learning Model to Enhance Critical Thinking Skills in Leadership Education (Literature Review): Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Kemampuan Berpikir Kritis pada Pembelajaran Kepemimpinan (Tinjauan Literatur) - Arifin; Sari, Mardiana; Sabaruddin; Nurmala, Eka; Sultan (PT. Alpha Trianguli Australis, 2024)
The aim of education is to provide an interesting and comfortable atmosphere for students to learn and achieve their goals. It is the duty of an educator to assess and understand the class in order to determine the best method to be used for teaching. The material taught in the class also plays a crucial role in determining the approach to be taken. Based on a systematic literature review (SLR), the problem-based learning model is an effective method for achieving educational goals and improving critical thinking skills in students. This model is also highly recommended for leadership learning in educational institutions because it fosters a sense of independence, democracy, and responsibility by developing students' potential.